Effects of different stabilization techniques on the shelf life of cold brew coffee: Chemical composition, flavor profile and microbiological analysis. (May 2021) - Bellumori, Maria; Angeloni, Giulia; Guerrini, Lorenzo; Masella, Piernicola; Calamai, Luca; Mulinacci, Nadia; Parenti, Alessandro; Innocenti, Marzia
Abstract: Cold brew coffee is a beverage prepared at low temperatures and over long brewing times resulting in particular physicochemical and sensory characteristics. This type of coffee is usually consumed immediately after preparation or after short storage in refrigerated conditions. However, in recent years many commercial coffee vendors started investing in ready-to-drink cold brew coffees packaged for extended storage. These products present the potential problem of microbial and sensorial alteration. In this study we evaluated five different stabilization techniques with the aim to extend the shelf life of the cold brew coffee while preserving its peculiar organoleptic properties, e.g. HPP (High Pressure Processing), microfiltration, UV irradiation, pasteurization and blast chilling process. The effects were investigated over four months, evaluating the caffeine and the chlorogenic acids contents by HPLC-DAD analysis and carrying out anevaluation of selected volatile compounds by HS-SPME-GC-MS. After four months of storage, the samples treated with pasteurization and HPP maintained a stable content of caffeine and chlorogenic acids, guaranteeing also the microbiological safety of the beverage. At the same shelf-time, the pasteurized samples showed an unaltered flavor profile, while a decrease of about 25% of the total content of volatile compounds was registered for the HPP sample. Highlights: Five physical treatments were evaluated to extend the shelf life of cold brew coffee. After four months of storage pasteurization and HPP guaranteed the safety of coffee. Pasteurization maintained chemical and sensory characteristics of coffee over time. All the treatments preserved bioactive compounds content and flavour profile at t0 . Blast-chilled and UV irradiated samples showed microbiological contamination at t1 .